Assessment of Oxidative Metabolism in Brown Fat Using PET Imaging - Muzik, Otto; Mangner, Thomas J.; Granneman, James G. (Frontiers in Endocrinology, 2012)
Objective: Although it has been believed that brown adipose tissue (BAT) depots disappear shortly after the perinatal period in humans, PET imaging using the glucose analog FDG has shown unequivocally the existence of functional BAT in humans. The objective of this study was to determine, using dynamic oxygen-15 (15O) PET imaging, to what extent BAT thermogenesis is activated in adults during cold stress and to establish the relationship between BAT oxidative metabolism and FDG tracer uptake. Methods: Fourteen adult normal subjects (9F/5M, 30+7 years) underwent triple oxygen scans (H215O, C15O, 15O2) as well as indirect calorimetric measurements at rest and following exposure to mild cold (60F). Subjects were divided into two groups (BAT+ and BAT-) based on the presence or absence of FDG tracer uptake (SUV > 2) in supraclavicular BAT. Blood flow (BF) and oxygen extraction fraction (OEF) was calculated from dynamic PET scans at the location of BAT, muscle and white adipose tissue (WAT). The metabolic rate of oxygen (MRO2) in BAT was determined and used to calculate the contribution of activated BAT to daily energy expenditure (DEE). Results: The median mass of activated BAT in the BAT+ group (5F, 31+8yrs) was 52.4 g (14-68g) and was 1.7 g (0-6.3g) in the BAT- group (5M/4F, 29+6yrs). SUV values were significantly higher in the BAT+ as compared to the BAT- group (7.4+3.7 vs 1.9+0.9; p=0.03). BF values in BAT were significantly higher in the BAT+ as compared to the BAT- group (13.1+4.4 vs 5.7+1.1 ml/100g/min, p=0.03), but were similar in WAT (4.1+1.6 vs 4.2+1.8 ml/100g/min) and muscle (3.7+0.8 vs 3.3+1.2 ml/100g/min). Calculated MRO2 values in BAT increased from 0.95+0.74 to 1.62+0.82 ml/100g/min in the BAT+ group and were significantly higher than those determined in the BAT- group (0.43+0.27 vs 0.56+0.24; p=0.67). The DEE associated with BAT oxidative metabolism was highly variable in the BAT+ group, with an average of 5.5+6.4 kcal/day (range 0.57–15.3 kcal/day).